2016
DOI: 10.18632/oncotarget.13674
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic secretory clusterin in hepatocellular carcinoma: Expression at early staging and emerging molecular target

Abstract: Secretory clusterin (sCLU) is associated with hepatocellular carcinoma (HCC) progression by contributing to angiogenesis, chemoresistance, cell survival, and metastasis. However, the sCLU expression at early stage of HCC progression remains to be clarified. In this study, the alteration of sCLU oncogenicity was firstly evaluated in HCC- and their para-cancerous- tissues. The incidence of sCLU expression in HCC was significantly higher than that in their non-tumorous tissues at message RNA (mRNA) or protein lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…It subsequently stimulates the downstream oncogenes to induce more aggressive phenotypes, including proliferation, metastasis and CSC phenotypes [28]. Our previous work and other studies demonstrated that sCLU could activate AKT and subsequently inactive GSK3β via phosphorylation in ser9 [17,29]. It has been investigated that GSK3β, a join-point between PI3K/AKT pathway and Wnt/βcatenin pathway, is essential for the stability of β-catenin in cytoplasm [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It subsequently stimulates the downstream oncogenes to induce more aggressive phenotypes, including proliferation, metastasis and CSC phenotypes [28]. Our previous work and other studies demonstrated that sCLU could activate AKT and subsequently inactive GSK3β via phosphorylation in ser9 [17,29]. It has been investigated that GSK3β, a join-point between PI3K/AKT pathway and Wnt/βcatenin pathway, is essential for the stability of β-catenin in cytoplasm [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…For sCLU silencing, the pRNAT-U6.1/Neo vector was generated previously by Biomics Company (Nantong, China) [17]. The sequences of shRNAs in this study were listed as follows: shRNA-1, 5′-GTA AGT ACG TCA ATA AGG A-3′;…”
Section: Plasmids and Transfectionmentioning
confidence: 99%
See 3 more Smart Citations